Pelaksanaan Ekstrakurikuler Paduan Suara Di SMP Adabiah Padang - Novia Mapriscka Utami; Ardipal Ardipal (CV. Aksara Global, 2024)
This research aims to describe the implementation of choir extracurricular activities at Adabiah Middle School in Padang. This type of research is qualitative research with a descriptive approach. The object of the research is the implementation of choir extracurricular activities at Adabiah Middle School in Padang. The research instrument is the researcher himself and is assisted by supporting instruments. Data analysis techniques by collecting data, clarifying data and concluding data. This research shows that the results of the extracurricular choir implementation at Adabiah Padang Middle School went quite well. This program is designed through structured stages, starting from providing information to students, registration, designing and determining the schedule, to selecting and presenting songs as well as grouping two types of high and low voices in the soprano and alto ranges. Each practice session includes teaching choral concepts, breathing techniques, voice production, and practice of the song